An Investigation of the Impact of COVID-19 on Food Access and Security in Bexar County: A Mixed Methods Approach - Olivia Chen; Corina Badillo; Dirk Wristers; Fozia Ali (SAGE Publishing, 2023)
Objectives: To investigate the effect of COVID-19 on food access and security in Bexar County, located within San Antonio, TX. Methods: To assess food insecurity levels and severity, we distributed a 10-min Qualtrics survey to San Antonio Food Bank (SAFB) clients. The survey was distributed between 19 October 2020 and 24 May 2021. Twenty-four survey respondents also participated in virtual focus group sessions over Zoom. Seven virtual focus group interviews were held between 15 January 2021 and 5 March 2021. Results: Survey results revealed that following COVID-19, 20.2% of SAFB clients were newly food insecure. 31.3% of survey respondents reported reduced wages and 28.8% reported job loss. Households experiencing job disruption from COVID-19 were 7 times at greater odds of being food insecure (OR 7.05; 95% CI, 1.61-30.88), as compared to those with stable employment. Major subthemes across focus group interviews included "excessive amounts of a single food item distributed," "long wait times for food," and "not receiving the type of food needed." Conclusions: Our study found evidence to support early studies' findings that COVID-19 has negatively impacted food security for many Americans. 70% of all unique Bexar County zip codes appeared in our survey analysis. Even beyond COVID-19's effect on food security, many other major societal changes were identified such as the increased reliance on technology, decreased in-person social gatherings, and greater mental health needs.